2016
DOI: 10.5957/jsr.2016.60.2.101
|View full text |Cite
|
Sign up to set email alerts
|

An Extended Verification and Validation Study of CFD Simulations for Planing Hulls

Abstract: In the context of marine application of computational fluid dynamic (CFD), it is well known that the numerical simulations of planing craft are significantly less reliable than that of displacement ships. For this reason, it is important to perform a comprehensive approach to the verification and validation (V&V) methodology and procedures for simulating CFD planing craft. In the first part of this paper, an assessment of the accuracy and effectiveness of different simulation setups and techniques for plan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 71 publications
(23 citation statements)
references
References 0 publications
0
23
0
Order By: Relevance
“…This procedure substitutes the estimated order of accuracy with 1 or 2 because the exponential power of error estimators to be selected (Equations ( 11) and ( 12)) is either 1 or 2. Slightly different from Eça and Hoekstra [31], De Luca et al [32] substitute p as the theoretical order of accuracy p th , i.e., p = p th = 2, when p * > 2. In fact, the method by De Luca et al [32] is more conservative, and it is applied in following calculations.…”
Section: Rementioning
confidence: 99%
See 1 more Smart Citation
“…This procedure substitutes the estimated order of accuracy with 1 or 2 because the exponential power of error estimators to be selected (Equations ( 11) and ( 12)) is either 1 or 2. Slightly different from Eça and Hoekstra [31], De Luca et al [32] substitute p as the theoretical order of accuracy p th , i.e., p = p th = 2, when p * > 2. In fact, the method by De Luca et al [32] is more conservative, and it is applied in following calculations.…”
Section: Rementioning
confidence: 99%
“…Considering that practical flow phenomenons are generally complex, and it is inevitable that p may be not in the range of [0.5, 2], Eça and Hoekstra [31] proposed another GCI method based on least-square roots (LSR-GCI). Such a method allows for error estimations even if the monotonic convergence is not achieved, and it is proven to be more reliable compared with GCI and CF based methods by De Luca et al [32]. Therefore, the LSR-GCI method [31] is applied for uncertainty estimations in this paper.…”
Section: Uncertainty Estimationmentioning
confidence: 99%
“…It is noteworthy to observe that the high percentage error for the dynamic sinkage is strictly connected to the small values of this parameter. For a more comprehensive picture about the validity of the results here exposed, it is possible to refer to the results shown in De Luca et al, 2016 [18], where the URANS CD-Adapco Star-CCM+ is used. The general trend shown in this last work is almost in line with the results obtained through the presented SPH model for the higher resolution; it is possible to recognize the same inaccuracy when dynamic trim predictions are considered.…”
Section: Total Resistance Dynamic Trim Angle and Sinkagementioning
confidence: 99%
“…De Luca et al, (2016) [18] showed the results of a comprehensive V&V campaign of simulations of resistance test in still water condition using the hulls of the warped planing hulls of the Naples Systematic Series. The analysis depicts, for a wide range of speed and different hull shapes, the simulation uncertainty and the comparison errors.…”
mentioning
confidence: 99%
“…The discretized governing equations are solved within active cells which update with the moving overset region. A linear interpolation scheme was used for linking the solution between the background region and the overset region for its efficiency and accuracy [17].…”
Section: Computational Domain and Boundary Conditionsmentioning
confidence: 99%